The regulatory role of adipocyte mitochondrial homeostasis in metabolism-related diseases - Song, Hongbing; Zhang, Xiaohan; Wang, Jing; Wu, Yanling; Xiong, Taimin; Shen, Jieqiong; Lin, Ruiyi; Xiao, Tianfang; Lin, Weimin (Frontiers in Physiology, 2023)
Adipose tissue is the most important energy storage organ in the body, maintaining its normal energy metabolism function and playing a vital role in keeping the energy balance of the body to avoid the harm caused by obesity and a series of related diseases resulting from abnormal energy metabolism. The dysfunction of adipose tissue is closely related to the occurrence of diseases related to obesity metabolism. Among various organelles, mitochondria are the main site of energy metabolism, and mitochondria maintain their quality through autophagy , biogenesis, transfer, and dynamics, which play an important role in maintaining metabolic homeostasis of adipocytes. On the other hand, mitochondria have mitochondrial genomes which are vulnerable to damage due to the lack of protective structures and their proximity to sites of reactive oxygen species (ROS) generation, thus affecting mitochondrial function. Notably, mitochondria are closely related to other organelles in adipocytes, such as lipid droplets and the endoplasmic reticulum, which enhances the function of mitochondria and other organelles and regulates energy metabolism processes, thus reducing the occurrence of obesity-related diseases. This article introduces the structure and quality control of mitochondria in adipocytes and their interactions with other organelles in adipocytes, aiming to provide a new perspective on the regulation of mitochondrial homeostasis in adipocytes on the occurrence of obesity-related diseases, and to provide theoretical reference for further revealing the molecular mechanism of mitochondrial homeostasis in adipocytes on the occurrence of obesity-related diseases.